Post humanity as an objective good: the dangers of futurism in the debate about enhancement of human genome - Vaccari, Andrés (Acta Bioethica, 2014)
The figure of posthumanity is invoked in a wide range of arguments that advertise the appeal or even the moral imperative of human enhancement through means of genetic engineering. Posthumanity is presented in these arguments as a highly beneficial state, the end point of a process of directed evolution to which we must devote our efforts. Focusing on the writings of transhumanist philosopher Nick Bostrom, in this article I question this normative role of posthumanity as a legitimation for liberal eugenics. For a start, I argue that the costs and benefits of a posthuman state are impossible to calculate. On the other hand, I identify certain problems concerning the positionality and instrumentality of augmented capacities. These capacities can be considered valuable inasmuch as they (1) provide an advantage relative to a context and (2) they are instrumental to the future benefit of persons. I argue that we cannot establish a necessary connection between capacities and wellbeing, thus the promise of posthumanity as a beneficial state is difficult to take seriously.